Paradoxes and sophisms in calculus - Klymchuk, Sergiy (Classroom resource materials., 2013)
In the study of mathematics, surprising and counter-intuitive examples can offer a fascinating insight into the development of the subject, and inspire a learner's passion for discovery. With a carefully-chosen selection of so-called paradoxes and sophisms, this book offers a delightful supplementary resource to enhance the study of single variable calculus. By paradox, the authors mean an unexpected statement that looks invalid, but is in fact true. The word sophism describes intentionally invalid reasoning that looks formally correct, but, in fact, contains a subtle mistake or flaw. This collection of over fifty paradoxes and sophisms showcases the subtleties of calculus and leads students to contemplate the underlying concepts. Sophisms and paradoxes from the areas of functions, limits, derivatives, integrals, sequences, and series are explored, with full explanations provided for each example. The book is an ideal resource for those studying or teaching calculus at high school and university level.